The association of hydrogen with nanometre bubbles of helium implanted into zirconium. (15th July 2018) - Blackmur, Matthew S.; Dumbill, Simon; MacLaren, Ian; Hernandez-Maldonado, David; Styman, Paul D.; Gass, Mhairi; Nicholls, Rebecca J.; Hyde, Jonathan M.; Ramasse, Quentin M.; Annand, Kirsty J.; Smith, James S.; Gotham, Natasha
Abstract: Electron energy-loss spectroscopy (EELS) is used to investigate the association of hydrogen with helium bubbles in zirconium. Conventional EELS data yield a signal at 13.5 eV (similar to the hydrogen K-edge, 13 eV), which is spatially distributed around the peripheries of bubbles and may correlate with the concentration of hydrogen/deuterium in the material. Ultra-high energy resolution EELS yields a signal at 148.6 meV (comparable to a range of ZrH bonds, 130–156 meV) from a region containing bubbles and no visible hydrides. These signals are interpreted in the context of either bubble surface chemisorption or bubble stress field trapping mechanisms. Graphical abstract: Unlabelled Image